2007
DOI: 10.1083/jcb.200702120
|View full text |Cite
|
Sign up to set email alerts
|

The yeast integral membrane protein Apq12 potentially links membrane dynamics to assembly of nuclear pore complexes

Abstract: Although the structure and function of components of the nuclear pore complex (NPC) have been the focus of many studies, relatively little is known about NPC biogenesis. In this study, we report that Apq12 is required for efficient NPC biogenesis in Saccharomyces cerevisiae. Apq12 is an integral membrane protein of the nuclear envelope (NE) and endoplasmic reticulum. Cells lacking Apq12 are cold sensitive for growth, and a subset of their nucleoporins (Nups), those that are primarily components of the cytoplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
148
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(168 citation statements)
references
References 53 publications
19
148
0
Order By: Relevance
“…Most notably, the pattern of genetic interactions with the APQ12 deletion is perfectly in line with the composition of the mammalian ESCRT-III complex involved in resealing of the nuclear envelope during mitosis. APQ12 mutants are defective in NPC assembly and in mRNA export at low temperature (20°); at higher temperatures, these processes are normal (Scarcelli et al 2007). We found that the Dchm7, Ddid2, Dsnf7, Dvps2, and Dvps24 mutants display a synthetic growth defect with the APQ12 deletion at elevated temperatures.…”
Section: Is Chm7 Part Of An Alternative Escrt-iii Complex?mentioning
confidence: 72%
See 2 more Smart Citations
“…Most notably, the pattern of genetic interactions with the APQ12 deletion is perfectly in line with the composition of the mammalian ESCRT-III complex involved in resealing of the nuclear envelope during mitosis. APQ12 mutants are defective in NPC assembly and in mRNA export at low temperature (20°); at higher temperatures, these processes are normal (Scarcelli et al 2007). We found that the Dchm7, Ddid2, Dsnf7, Dvps2, and Dvps24 mutants display a synthetic growth defect with the APQ12 deletion at elevated temperatures.…”
Section: Is Chm7 Part Of An Alternative Escrt-iii Complex?mentioning
confidence: 72%
“…This suggests that the Chm7 complex and Apq12 could have a common target. Evidence has been presented that Dapq12 mutants are defective in the ability to adjust membrane lipid composition in response to low temperature, which could lead to the observed defects in NPC assembly and mRNA export (Scarcelli et al 2007). The CHM7 deletion, however, does not show a NPC assembly defect at any temperature (not shown).…”
Section: Is Chm7 Part Of An Alternative Escrt-iii Complex?mentioning
confidence: 99%
See 1 more Smart Citation
“…While this model clearly requires extensive experimental evidence to prove, it makes the prediction that lumenal vesicles would be more prevalent under conditions in which INM-ONM fusion is attenuated. One could interpret the lumenal vesicles observed in apq12, 45 acc1, 51 gle2, 52 and nup116 53 strains in such a framework. This model would also support that membrane fusion is a commitment step in NPC formation, and might explain why malformed NPCs accumulate in the SINC, instead of being removed and degraded.…”
Section: Does Escrt-iii Directly Contribute To Npc Biogenesis?mentioning
confidence: 99%
“…[39][40][41][42] Lastly, biochemical intermediates and invaginations of the INM have been observed after the genetic imposition of assembly blocks. [43][44][45] While proteins of the reticulon family 27,28 and nups capable of deforming membranes 46,47 might generate positive membrane curvature that could help form these invaginations, it has been appropriately argued that the generation of negative curvature might be more effective in promoting the formation of a nuclear pore, 48 precisely the kind of curvature that would be compatible with an ESCRT-III mediated mechanism.…”
Section: Does Escrt-iii Directly Contribute To Npc Biogenesis?mentioning
confidence: 99%